A comparative study to evaluate the technical performance according to some kinematic variables for the national team players in the shot put for the disabled ((F40 (Journal of the College of Basic Education, 2023)
The presence of the disabled is a tangible fact, and the developed societies are working to integrate this segment of society into the future planning strategy, as their full energies can be utilized in various fields, as the interest of societies in this segment is one of the main indicators for judging the degree of their scientific, human and civilized progress.And Muhammad Kamel Omar (1998) () mentions that the number of disabled people is constantly increasing, as the reports of the World Health Organization mentioned that the number of disabled people in the world is estimated at about (600) million disabled people.The world is currently witnessing a remarkable growth in the interest in the sport of the disabled, as the practice of sport for them is no longer limited to the recreational and therapeutic aspect only, but rather the sport competition and the podiums have become a goal that the disabled seek to reach.Halim al-Jabali (2002) stated that the development witnessed by the Olympic Games for the Disabled is the result of the countries' interest in participating or competing, as these games represent the second largest sporting event in the world in terms of the number of participants after the Olympic Games for the unfit. The best evidence is the amount of growth in the number of participating countries as well as athletes, as the first Olympic Games in 1960 in Rome had the participation of 400 athletes from 123 countries.